Supplier Performance Enhancement for Sugar Product Competitiveness at PG. Rajawali II, Sindanglaut Unit, Cirebon Regency - Uljanah, Lulu; Azhar, Lea Haifa; Khaliq, Ruly Irfan Nur; Hidayat, Yayat Rahmat (Dinasti Publisher, 2025)
This study aims to analyze the influence of contract farming, information sharing, and communication quality on supplier performance and its impact on sugar product competitiveness at PG. Rajawali II Sindanglaut Unit, Cirebon Regency. The research method used was quantitative with a survey approach involving 110 sugarcane farmers selected through proportional random sampling. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results indicate that contract farming, information sharing, and communication quality significantly affect supplier performance. Furthermore, supplier performance is proven to enhance sugar product competitiveness. The contract farming variable contributes the largest total effect (0.417), followed by communication quality (0.460) and information sharing (0.179). These findings confirm that effective collaboration between farmers and sugar factories, supported by transparent communication and accurate information sharing, is a key factor in improving product competitiveness. The implications of this study highlight the need to strengthen partnerships through sustainable contract farming, enhanced information access, and improved communication quality between suppliers and producers.